Super science encyclopedia - Challoner, Jack (DK Publishing, 2021)
Provides an illustrated encyclopedia highlighting the science behind all aspects of life, from vaccines and batteries to cranes and telescopes. Discusses the scientific method, the fields of science, and the practical use of science in our daily lives. Includes dozens of color photographs, fact boxes, and a glossary of terms.